1991
DOI: 10.1111/j.1476-5381.1991.tb12371.x
|View full text |Cite
|
Sign up to set email alerts
|

The neuroprotective action of dizocilpine (MK‐801) in the rat middle cerebral artery occlusion model of focal ischaemia

Abstract: 1 An acute model of focal ischaemia, which involves permanent occlusion of the middle cerebral artery of the rat with 4 h survival, was used to find the minimum effective plasma concentration of dizocilpine (MK-801) and to determine its dose-effect relationship. 2 MK-801 was administered at the time of occlusion and was given as an i.v. bolus followed by an infusion for 4 h to maintain a steady state plasma concentration of the drug throughout the study.MK-801 was given at 3 dose levels; 0.04mgkg-1 i.v. bolus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
1
1

Year Published

1993
1993
2018
2018

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 126 publications
(59 citation statements)
references
References 40 publications
1
56
1
1
Order By: Relevance
“…The present studies indicate that the doses of dizocilpine required for optimal neuroprotection (Gill et al, 1991b) are at the threshold of those for inducing changes in neuronal morphology since one of four rats showed a vacuolation response. Thus, there is little margin between wanted and unwanted effects with dizocilpine.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…The present studies indicate that the doses of dizocilpine required for optimal neuroprotection (Gill et al, 1991b) are at the threshold of those for inducing changes in neuronal morphology since one of four rats showed a vacuolation response. Thus, there is little margin between wanted and unwanted effects with dizocilpine.…”
Section: Discussionmentioning
confidence: 90%
“…using fluorescence detection after solid phase extraction and pre-column derivatisation with FMOC chloride. Plasma dizocilpine levels resulting from the present dosing regimes have been reported previously (Gill et al, 1991b).…”
Section: Plasma Drug Levelsmentioning
confidence: 85%
See 1 more Smart Citation
“…It has been suggested that neuroprotective doses of MK-801 (0.3-0.8 mg/kg; i.p.) block NMDA receptors in the brain, and these doses produce plasma concentrations within the range of NMDA receptor affinity (Gill et al, 1991;Massieu et al, 1993).…”
Section: Methodsmentioning
confidence: 99%
“…The failure of nitrendipine to protect against glutamate neurotoxicity would suggest that L-type calcium channels are not involved in the evolution of this insult under the present experimental conditions, although a report by Weiss et al (1990) shown to reduce the neuronal damage produced by cerebral ischaemia in animal models. These agents include NMDA antagonists (Park et al, 1988;Gill et al, 1991), non-NMDA excitatory amino acid receptor antagonists (Sheardown et al, 1990;but see DeGraba et al, 1994), calcium and sodium channel inhibitors (Steen et al, 1985;Alps et al, 1988;Pauwels et al, 1991) and inhibitors of lipid peroxidation (Hall et al, 1988;Young et al, 1988 cultures. The anticonvulsant agent and sodium channel inhibitor, phenytoin, has been shown to enhance recovery of synaptic transmission in rat hippocampal slices under conditions of simulated ischaemia (Kenny & Sheridan, 1992).…”
Section: Discussionmentioning
confidence: 99%